Bioinspired Pollen‐Like Hierarchical Surface for Efficient Recognition of Target Cancer Cells. Issue 15 (4th May 2017) - Wang, Wenshuo; Yang, Gao; Cui, Haijun; Meng, Jingxin; Wang, Shutao; Jiang, Lei
Abstract : The efficient recognition and isolation of rare cancer cells holds great promise for cancer diagnosis and prognosis. In nature, pollens exploit spiky structures to realize recognition and adhesion to stigma. Herein, a bioinspired pollen‐like hierarchical surface is developed by replicating the assembly of pollen grains, and efficient and specific recognition to target cancer cells is achieved. The pollen‐like surface is fabricated by combining filtering‐assisted assembly and soft lithography‐based replication of pollen grains of wild chrysanthemum. After modification with a capture agent specific to cancer cells, the pollen‐like surface enables the capture of target cancer cells with high efficiency and specificity. In addition, the pollen‐like surface not only assures high viability of captured cells but also performs well in cell mixture system and at low cell density. This study represents a good example of constructing cell recognition biointerfaces inspired by pollen–stigma adhesion. Abstract : A pollen‐like hierarchical surface is developed by combining a filtering‐assisted assembly method and soft lithography. The as‐prepared surface can enable the capture of target cancer cells with high efficiency and specificity after modification with recognition agent. The work represents a good example of constructing cell recognition biointerfaces inspired by pollen–stigma adhesion.